a) 3x - 8 = 16
3x = 16 + 8
3x = 24 |÷3
x = 8
b) 2x + 19 = x + 25
2x - x = 25 - 19
x = 6
c) 4x - 23 = 2x + 1
4x - 2x = 1 + 23
2x = 24 |÷2
x = 12
d) 8x + 10 = - 6
8x = - 6 - 10
8x = -16 |÷8
x = -2
e) 5 + 3x = x - 9
3x - x = - 9 - 5
2x = - 14 |÷2
x = - 7
f) 6x - 2x + 7 = - 25
6x - 2x = - 25 - 7
4x = - 32 |÷4
x = - 8
g) 7x - 12 = -2x - 3
7x + 2x = -3 + 12
9x = 9 |÷9
x = 1
h) 3 - 4x = -9
- 4x = - 9 - 3
- 4x = - 12 |÷ (- 4)
x = 3
i) 5x = - 8 - 3x
5x + 3x = -8
8x = -8 |÷8
x = - 1
j) - 35 = 9x - 1
nie wiem niestety :(
k) 6x - 5 = -3x + 13
6x + 3x = 13 + 5
9x = 18 |÷ 9
x = 2